Cestrum parqui poisoning in cattle in Northwestern Argentina: report of 10 outbreaks - Ruiz, Álvaro Francisco; Medina, Diego Martín Nicolás; Colque Caro, Luis Adrián; Avellaneda Cáceres, Agustín; Aguirre Castro, Laura Sabrina; Sandoval, Gabriela Virginia; Micheloud, Juan Francisco (Ediciones INTA, 2024)
Cestrum parqui is a perennial plant known for its toxicity in ruminants. This work describes several outbreaks of natural intoxication with C. parqui from different sources, affecting cattle in different production systems, with morbidity rates varying from 2,7% and 25%. Clinical signs included tremors in the hindquarters, recumbency, and death. The liver showed swelling, congestion, and a mottled appearance. Histopathological findings consisted mainly of hemorrhagic centrilobular hepatocellular necrosis.